Impact of Gamification on Consumers' Favorability in Cause-Related Marketing Programs: Between-Subjects Experiments - Yanhe Li; Yanchen Li; Xiu Zhou; Kunshu Ma (JMIR Publications, 2023)
BackgroundSuccessful cause-related marketing (CRM) campaigns can help companies stand out from their competitors; however, CRM may not have pleasant outcomes, even if it receives substantial investment. ObjectiveThis research aimed to investigate how gamified CRM projects influence consumers' favorability. MethodsWe introduced 3 different CRM projects in 3 different studies. Every project had 2 versions according to the level of gamification, and participants were randomly assigned into these 2 groups. Additionally, we used a 2 (gamification: lower, higher) 2 (rules presentation: without visual cues, with visual cues) between-subjects design to test the moderation role of rules presentation in gamified CRM projects. ResultsIn Study 1, we identified that the highly gamified CRM program induces more enjoyment (F1,139=21.11, P<.001) and higher favorability (F1,139=14.57, P<.001). Moreover, we found that enjoyment played a mediation role between gamification and favorability (P<.001) in Study 2. In addition, the results of Study 3 indicated rules presentation in a gamified CRM program can moderate the indirect effect of gamification on favorability via enjoyment (index of the moderated mediation: 95% CI -1.12 to -0.10; for rules presentation with visual cues: 95% CI 0.69 to 1.40; for rules presentation without visual cues: 95% CI 0.08 to 0.83). ConclusionsOverall, this research contributes to the CRM literature and suggests gamification is an effective way of managing CRM campaigns.